Marx's scientific dialectics : a methodological treatise for a new century - Paolucci, Paul (Studies in critical social sciences, 2007)
Examines both problems in traditional readings of Marx's texts and how he used several methods of science to inform his dialectical thinking, historical materialist research, political economic analyses, and his communist project.